2005
DOI: 10.1007/s11181-005-0199-1
|View full text |Cite
|
Sign up to set email alerts
|

The Field of a Finite Defect in a 3D Semispace

Abstract: The field of an arbitrary finite defect in a 3D semispace is calculated. This problem is solved by reduction to a 2D case that yields an integral equation on the surface of the defect alone. Calculation formulas for a spherical defect are presented. Results of calculations using these formulas for the case of a uniform external field normal or tangential to the surface of a magnetic semispace are presented in a graphical form.Solving the magnetostatic problem for different models of bodies containing defects r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…So, according to the voltage and phase of the transducer, some information about surface crack can be acquired. [1,2,3,11,12,13] Eddy current sensor is based on electromagnetic field theory, so the qualitative relationship between output of eddy current sensor and surface crack can be described by Maxwell electromagnetic field theory. Many research papers have reported it.…”
Section: Analysis Of the Relationship Between Crack And Signal Inmentioning
confidence: 99%
See 1 more Smart Citation
“…So, according to the voltage and phase of the transducer, some information about surface crack can be acquired. [1,2,3,11,12,13] Eddy current sensor is based on electromagnetic field theory, so the qualitative relationship between output of eddy current sensor and surface crack can be described by Maxwell electromagnetic field theory. Many research papers have reported it.…”
Section: Analysis Of the Relationship Between Crack And Signal Inmentioning
confidence: 99%
“…Many research papers have reported it. [1,2,3,7,8,9,10,11,12,13] The appearance of a crack will change transducer impedance. The amplitude component (Z) of transducer impedance is in non-linear with the crack depth, while the phase component is in linear with the crack depth.…”
Section: Analysis Of the Relationship Between Crack And Signal Inmentioning
confidence: 99%